2015
DOI: 10.5513/jcea01/16.2.1611
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and correlation studies in some drought-resistant sunflower (Helianthus annuus L.) genotypes

Abstract: Five sunflower hybrids (Albena, Super Start, Zora, Santafe and San Luka) and their parental lines (2607, 1234, 1607 were tested on a block design in four replication in the course of two years. The highest phenotypic and genotypic coefficients of variation were recorded for seed yield per plant followed by the number of seeds per plant and 1000 seed weight, while the lowest value was observed at 50% flowering. The heritability coefficients in a broad sense were high in all characters and ranged from 69.74 % to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
1
5
0
1
Order By: Relevance
“…According to Pandya et al (2015), oil content showed negative non-significant correlation with days to maturity, stem diameter, number of leaves per plant, plant height, and 100 seed weight. Yankov & Tahsin (2015) found negative but not significant correlation between oil content and head diameter while positive correlation was found between oil content and plant height. These authors concluded that seed yield could be increased by selection of plant height, stem diameter and number of seeds, because they had a high positive correlation with seed yield and they also showed high heritability.…”
mentioning
confidence: 70%
“…According to Pandya et al (2015), oil content showed negative non-significant correlation with days to maturity, stem diameter, number of leaves per plant, plant height, and 100 seed weight. Yankov & Tahsin (2015) found negative but not significant correlation between oil content and head diameter while positive correlation was found between oil content and plant height. These authors concluded that seed yield could be increased by selection of plant height, stem diameter and number of seeds, because they had a high positive correlation with seed yield and they also showed high heritability.…”
mentioning
confidence: 70%
“…About 10% of the world's annual sunflower production is destined for non-oil purposes, this demand being met by confectionery genotypes that are characterized by having greater stature of larger plants and seeds with lower oil contents and higher protein contents (HlADNI et al, 2011). Height of plants is one of the most important characters for confectionery sunflower genotypes (PEKCAN et al, 2015;HlADNI et al, 2016), as it correlates with characters such as stem diameter, number of leaves, chapter diameter, seed yield per plant and oil and protein contents (PIVETTA et al, 2012;YANKOV & TAHSIN, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our whole system of agriculture depends on many important ways and microbial activities appear to be a tremendous potential for making use of microorganisms in increasing crop production [15,[16][17]. Recently many researchers [1,6,[18][19][20][21][22]] noticed significant differences among sunflower genotypes in growth and yield traits and also reported that sunflower hybrids surpassed local varieties or cultivars in yield and its components [23] reported that, in the Sudan, virtually 98% of oilseed sunflower production depends on hybrids, which has intensified the interest of farmers and other producers to grow the crop, Also, they reported that, the area under sunflower cultivation in the Sudan had shown an increasing manner in the last ten years. Meager studies have been conducted on the effects of biofertilizer on sunflower hybrids in Sudan.…”
Section: Introductionmentioning
confidence: 99%